The Use of Artificial Intelligence for Marketing Community Economic Products in West Sumatra - Awaluddin, Awaluddin; Annas, Firdaus; Yuspita, Yulifda Elin (Islamic Studies and Development Center in Collaboration With Students' Research Center Universitas Negeri Padang, 2025)
The development of digital technology has brought significant changes in various aspects of life, including marketing. Artificial Intelligence is one of the innovations that play a role in increasing marketing effectiveness, especially for small and medium enterprises. This research aims to analyze the use of Artificial Intelligence in marketing community economic products in West Sumatra, or identify the benefits and challenges faced by business actors in applying Artificial Intelligence technology to market their products. The method used in this research is a qualitative approach with interview and observation techniques. Data was collected from small and medium enterprises in West Sumatra that have used Artificial Intelligence in their marketing strategies. The results showed that the application of Artificial Intelligence in marketing community economic products in West Sumatra has a positive impact. The use of Artificial Intelligence in marketing has great potential in increasing the competitiveness of local products and expanding the market for businesses in West Sumatra. Thus, the use of Artificial Intelligence in marketing can be an innovative solution in encouraging economic growth in the region.